Infographic of Internet Usage Data for Learning Process in the Province of Indonesia - Nofirman; Pandu Adi Cakranegara; Diana Yusuf; Nanny Mayasari; Arifin (Institute of Computer Science (IOCS), 2022)
The development of telecommunications in Indonesia has significantly affected the emergence of the digital age, as the internet has become a daily necessity for community activities. Information and communication technology (ICT)-based learning is influencing teaching methods and learning media to use the internet for the learning process in the field of education. This study aims to analyze and graphically present data on the internet usage of rural and urban residents in all Indonesian provinces concerning their education levels. The presented data is in the form of types of internet usage that support the learning process so that it can become predominant in the use of the internet by rural and urban areas and serve as a positive input for internet service providers in the improvement of education-related services. The results indicated that using the Internet to support the learning process by communities in rural and urban areas of Indonesian provinces is one of the goals of using the Internet to obtain information for the learning process is 10%. D.I.Yogyakarta has the highest percentage 58,1%, indicating the most significant number of internet users for educational purposes. When students and student users access the internet to support the learning process, they engage in a variety of activities, including doing assignments, accessing e-learning tools, accessing media information to support learning, using web browsers to display social media, and accessing e-mail to submit assignments using smartphone media, which is the most prevalent form of internet access.